STATUS ANAK DI LUAR NIKAH DALAM PERSPEKTIF SEJARAH SOSIAL - Abdillah, Kudrat (State Islamic University (UIN) Ar-Raniry, 2016)
In literature of Islamic jurisprudence, children born outside marriage consider to have family line with their mother. It also has similarity with Indonesian’s law stating in the Marriage Act and the Compilation of Islamic Law. The significant changes occur after judgment of Constitutional Court No. 46/PUU-VIII/2010, stating that children outside of marriage have also family line with their father, as long as can be proofed biologically through science and technology and/or other evidences. This article use historical social approach to analyse a legal history of Constitutional Court judgment. The writer personally argues that Constitutional Court considers the welfare of children as justification of family line with father. The advance development in science and technology such as using Desoxyribo Nucleic Acid (DNA) can give evidence in searching the family’s line. This consideration gives a strong legal background for Constitutional Court to protect private rights of children born outside marriage.